Eye-tracking of visual attention in web-based assessment using the Force Concept Inventory. (8th May 2017) - Han, Jing; Chen, Li; Fu, Zhao; Fritchman, Joseph; Bao, Lei
Abstract: This study used eye-tracking technology to investigate students' visual attention while taking the Force Concept Inventory (FCI) in a web-based interface. Eighty nine university students were randomly selected into a pre-test group and a post-test group. Students took the 30-question FCI on a computer equipped with an eye-tracker. There were seven weeks of instruction between the pre- and post-test data collection. Students' performance on the FCI improved significantly from pre-test to post-test. Meanwhile, the eye-tracking results reveal that the time students spent on taking the FCI test was not affected by student performance and did not change from pre-test to post-test. Analysis of students' attention to answer choices shows that on the pre-test students primarily focused on the naïve choices and ignored the expert choices. On the post-test, although students had shifted their primary attention to the expert choices, they still kept a high level of attention to the naïve choices, indicating significant conceptual mixing and competition during problem solving. Outcomes of this study provide new insights on students' conceptual development in learning physics.